Multilayer film
Patent Information
- Application Number
- CN202380032620.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-06
- Filing Date
- 2023-04-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-04-04
Smart Images

Figure QLYQS_1 
Figure BDA0005071324790000091 
Figure BDA0005071324790000092
Abstract
Description
[0001] This invention relates to a specific multilayer film comprising a surface layer (SKL), a core layer (CL), and a sealing layer (SL), wherein the core layer (SL) comprises (a) 5 to 40 wt% of a specific metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL) and (b) 60 to 95 wt% of a specific multimodal Ziegler-Natta-catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL), wherein components (a) and (b) together comprise at most 100 wt%. The invention also relates to the use of said multilayer film as a packaging material.
[0002] Polyethylene is widely used in various aspects of daily life, such as packaging, due to its excellent cost-effectiveness. Due to varying needs, multi-layered products made of different types of materials are now used, which satisfies these needs to some extent, but the drawback is the difficulty in recycling such products. From a recycling perspective, single-material solutions would be the preferred choice. At the same time, the material's performance should not be compromised.
[0003] Multilayer films and sealing compositions for producing such films are known in the prior art.
[0004] WO 2012 / 061168 A1 relates to a sealant composition, a method for preparing the same, articles made therefrom, and a method for forming such articles. The sealant composition comprises: (a) 70 to 99.5 wt% of an ethylene / α-olefin interpolymer composition based on the total weight of the sealant composition, wherein the ethylene / α-olefin interpolymer composition comprises an ethylene / α-olefin interpolymer, wherein the ethylene / α-olefin interpolymer has a comonomer distribution constant (CDC) in the range of 15 to 250, and in the range of 0.875 to 0.963 g / cm³. 3 (a) a density in the range of 0.2 to 20 g / 10 min, a melt index (I2) in the range of 0.02 to 3 long chain branches (LCB) / 1000°C, and (b) 0.5 to 30 wt% of a propylene / α-olefin interpolymer composition, wherein the propylene / α-olefin interpolymer composition comprises a propylene / α-olefin copolymer or a propylene / ethylene / butene terpolymer, wherein the propylene / α-olefin copolymer has a crystallinity in the range of 1 wt% to 30 wt%, a heat of fusion in the range of 2 joules / g to 50 joules / g, and a DSC melting point in the range of 25°C to 110°C.
[0005] EP 0 575 465 A1 relates to heat-sealing compositions suitable for membranes and membrane structures, comprising: (a) 30 to 70 wt% of a low-melting-point polymer having a density of 0.88 g / cm³. 3 Up to 0.915 g / cm 3(a) an ethylene-based copolymer with a melt index of 1.5 dg / min to 7.5 dg / min, a molecular weight distribution of no more than 3.5 and a compositional width index of more than 70%; and (b) 70 to 30 wt% of a propylene-based copolymer different from (a), having 88 mol% to 100 mol% propylene and 12 mol% to 0 mol% α-olefins other than propylene.
[0006] WO 2021 / 204799 A1 relates to a membrane comprising a sealing layer comprising polyethylene A, the polyethylene A comprising a portion derived from ethylene and a portion derived from an α-olefin comprising 4 to 10 carbon atoms, the polyethylene A having a weight of ≥870 and ≤920 kg / m³. 3 Preferably ≥900 and ≤920 kg / m 3 The density is determined according to ASTM D792 (2013), wherein polyethylene A has: a material fraction eluted in analytical temperature rise elution fractionation (a-TREF) at a temperature ≤30.0°C, representing ≥5.0 wt% and ≤15.0 wt%, preferably ≥7.5 wt% and ≤12.5 wt% of the total weight of polyethylene; and two distinct peaks in the a-TREF curve within the elution temperature range of 50.0 to 90.0°C, wherein the elution temperature difference between the two peaks is ≤17.5°C, preferably ≤15.0°C.
[0007] Therefore, one object of the present invention is to provide a multilayer membrane that is not only easy to recycle, but also has a good balance between mechanical properties and sealing properties.
[0008] This objective has been achieved by a multilayer film according to claim 1, the multilayer film comprising a surface layer (SKL), a core layer (CL), and a sealing layer (SL); wherein the core layer (CL) comprises
[0009] (a) 5 to 40 wt% of a metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL), which has
[0010] • Between 880 and 925 kg / m 3 Density within the specified range (ASTM D792);
[0011] • MFR2 (190℃, 2.16kg, ISO 1133) in the range of 0.1 to 6.0 g / 10 min; and
[0012] MFR in the range of 22 to 70 21 The ratio of (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO 1133), MFR 21 / MFR2; and
[0013] (b) 60 to 95 wt% of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL), which has
[0014] • Between 925 and 950 kg / m 3 Density within the range (ASTM D792); and
[0015] • MFR5 (190℃, 5kg, ISO 1133) in the range of 0.1 to 6.0 g / 10 min; where
[0016] The sum of components (a) and (b) is at most 100 wt%.
[0017] Advantageous embodiments of the multilayer film according to the invention are described in detail in dependent claims 2 to 14. The invention also relates to the use of the article according to the invention as a packaging material according to claim 15.
[0018] definition
[0019] Metallocene-catalyzed (linear low-density) polyethylene is defined in this invention as a (linear low-density) polyethylene copolymer produced in the presence of a metallocene catalyst.
[0020] Ziegler-Natta catalyzed (linear low-density) polyethylene is defined in this invention as a linear low-density polyethylene copolymer produced in the presence of a Ziegler-Natta catalyst.
[0021] For the purposes of this invention, metallocene-catalyzed (linear low-density) polyethylene can be composed of an ethylene-1-butene polymer component (A) and an ethylene-1-hexene polymer component (B). This refers to the polymer being produced in a sequential polymerization process of at least two stages, wherein component (A) is first produced, and then component (B) is produced in a subsequent polymerization step in the presence of component (A) to produce metallocene-catalyzed (linear low-density) polyethylene, or vice versa, i.e., component (B) is first produced, and then component (A) is produced in a subsequent polymerization step in the presence of component (B) to produce metallocene-catalyzed (linear low-density) polyethylene.
[0022] In the context of multimodal metallocene-catalyzed (linear low-density) polyethylene or Ziegler-Natta-catalyzed (linear low-density) polyethylene, the term "multimodal" herein refers to the multimodality with respect to the melt flow rate (MFR) of at least ethylene polymer components (A) and (B), i.e., ethylene polymer components (A) and (B) have different MFR values. Multimodal metallocene-catalyzed (linear low-density) polyethylene may exhibit additional multimodality between ethylene polymer components (A) and (B) with respect to one or more other properties (such as density, comonomer type, and / or comonomer content), which will be described below.
[0023] In the context of this invention, the homopolymer may contain up to 3.0 mol% of copolymer, preferably up to 2.0 mol%, of the total weight of the homopolymer based on the comonomer, but may also be copolymer-free.
[0024] In the context of this invention, a single-material membrane can be a membrane that primarily uses one polymer (e.g., polyethylene) but does not use a large number of other polymers. However, in the case where the membrane is based on polyethylene, different types of polyethylene can be used.
[0025] Low-density polyethylene (LDPE) is defined in this invention as a low-density polyethylene copolymer preferably produced in a high-pressure process.
[0026] When the term "comprising" is used in this specification and claims, it does not exclude other unspecified elements of primary or secondary functional importance. For the purposes of this invention, the term "consisting of" is considered a preferred embodiment of the term "comprising." If a group is defined below as including at least a certain number of embodiments, this should also be understood as a disclosed group, which preferably consists only of these embodiments.
[0027] Whenever the terms “including” or “having” are used, these terms mean the same as “include” as defined above.
[0028] When referring to a singular noun, use the indefinite or definite article, such as "a", "an", or "the / that", unless otherwise specified, this includes the plural form of the noun.
[0029] Metallocene-catalyzed multimodal polyethylene copolymers (MMCP)
[0030] The core layer (CL) of the multilayer film according to the invention comprises 5 to 40 wt% of a specific metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL). Other layers may also comprise said copolymer (MMCP).
[0031] Multimodal polyethylene copolymers (MMCPs) have a concentration of 880 to 925 kg / m³. 3Density within the range (ASTM D792), MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.1 to 6.0 g / 10 min; and MFR in the range of 22 to 70. 21 The ratio of (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO 1133), MFR 21 / MFR2.
[0032] According to a preferred embodiment of the present invention, the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) comprises: an ethylene polymer component (A), preferably a copolymer of ethylene and 1-butene, more preferably composed of an ethylene polymer portion (A-1) and an ethylene polymer portion (A-2); and an ethylene polymer component (B), preferably a copolymer of ethylene and 1-hexene.
[0033] In a preferred embodiment of the invention, the ethylene-1-butene polymer component (A) is composed of ethylene polymer portions (A-1) and (A-2).
[0034] When the ethylene-1-butene polymer component (A) is composed of ethylene polymer portions (A-1) and (A-2), the MFR2 of the ethylene polymer portions (A-1) and (A-2) may be the same or different from each other.
[0035] According to another preferred embodiment of the invention, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A-1) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 1.0 to 15.0 g / 10 min or 100 to 140 g / 10 min, preferably 1.5 to 13.0 g / 10 min or 110 to 130 g / 10 min, more preferably 2.0 to 11.0 g / 10 min or 115 to 125 g / 10 min, and even more preferably 2.5 to 10.5 g / 10 min or 117 to 124 g / 10 min.
[0036] In another preferred embodiment of the present invention, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A-2) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 2.0 to 30.0 g / 10 min or 100 to 140 g / 10 min, preferably 2.5 to 20.0 g / 10 min or 110 to 130 g / 10 min, more preferably 3.0 to 15.0 g / 10 min or 115 to 125 g / 10 min.
[0037] According to another preferred embodiment of the invention, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 2.0 to 30.0 g / 10 min or 100 to 140 g / 10 min, preferably 2.5 to 20.0 g / 10 min or 110 to 130 g / 10 min, more preferably 3.0 to 15.0 g / 10 min or 115 to 128 g / 10 min, and even more preferably 3.2 to 10.0 g / 10 min or 120 to 125 g / 10 min.
[0038] Other preferred embodiments of the invention specify that the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (B) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 0.01 to 1.5 g / 10 min or 0.001 to 1.5 g / 10 min, preferably 0.05 to 1.2 g / 10 min, more preferably 0.1 to 1.0 g / 10 min, and even more preferably 0.2 to 0.7 g / 10 min.
[0039] In a preferred embodiment, the MFR2 of the ethylene polymer components (A) and (B) are different from each other.
[0040] According to another preferred embodiment of the invention, the MFR2 (190°C, 2.16 kg, ISO 1133) of the multimodal copolymer (MMCP) is in the range of 0.1 to 2.0 g / 10 min, preferably 0.2 to 1.7 g / 10 min, and more preferably 0.5 to 1.0 g / 10 min.
[0041] According to another preferred embodiment of the invention, the ratio of the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer component (A) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) to the MFR2 (190°C, 2.16 kg, ISO 1133) of the MMCP is in the range of 2.5 to 20.0, preferably 3.0 to 15.0, and more preferably 3.5 to 10.0.
[0042] In another preferred embodiment of the invention, the density (ASTM D792) of the ethylene polymer component (A) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is between 920 and 950 kg / m³. 3 Preferred weight is 925 to 950 kg / m³. 3 More preferably 930 to 945 kg / m 3 Within the range.
[0043] Other preferred embodiments of the invention specify that the density (ASTM D792) of the ethylene polymer portion (B) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is between 880 and 915 kg / m³. 3 Preferred weight is 885 to 910 kg / m³. 3 More preferably 890 to 905 kg / m 3 Within the range.
[0044] According to another preferred embodiment of the invention, the density (ASTM D792) of the polymer portion (A-1) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is between 920 and 960 kg / m³. 3 Preferred weight is 925 to 955 kg / m³. 3 More preferably 930 to 950 kg / m 3 Within the range.
[0045] According to another preferred embodiment of the invention, the density (ASTM D792) of the polymer portion (A-2) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is between 930 and 950 kg / m³. 3 Preferred weight is 935 to 945 kg / m³. 3 Within the range.
[0046] In another preferred embodiment, the density (ASTM D792) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is between 900 and 925 kg / m³. 3 Preferred weight is 910 to 925 kg / m³. 3 Within the range.
[0047] Of course, in addition to the multimodality of MFR2 (i.e., differences between them) of ethylene polymer components (A) and (B), the multimodal PE of the present invention may also be multimodal, for example, with respect to one or both of two other properties: the content of comonomers present in ethylene polymer components (A) and (B); and / or the multimodality of the density of ethylene polymer components (A) and (B), i.e., differences between them.
[0048] Preferably, the multimodal copolymer (MMCP) is further multimodal in terms of the comonomer content of the ethylene polymer components (A) and (B).
[0049] The polymer parts (A-1) and (A-2) have the same type of comonomer, so both parts have 1-butene as a comonomer.
[0050] The comonomer content of components (A) and (B) can be measured, or, in a preferred case, in a so-called multi-stage method, one component is first produced, and then another component is produced in the presence of the first component. The comonomer content of the first produced component, such as component (A), can then be measured, and the comonomer content of the other component, such as component (B), can be calculated according to the following equation:
[0051] Comonomer content in component B (wt% or mol%) = (Comonomer content in the final product (wt% or mol%) - (Weight fraction of component A) * Comonomer content in component A (wt% or mol%)
[0052] / (Weight fraction of component B).
[0053] Another preferred embodiment of the invention specifies that the total amount of 1-butene based on MMCP is in the range of 0.1 to 1.5 wt%, preferably 0.2 to 1.3 wt%, more preferably 0.4 to 1.2 wt% or 0.4 to 0.6 wt%, and / or the total amount of 1-hexene based on MMCP is in the range of 2.0 to 20.0 wt%, more preferably 4.0 to 18.0 wt%, and even more preferably 6.0 to 15.0 wt%.
[0054] According to another preferred embodiment of the invention, the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is composed of (i) 35.0 to 50.0 wt% of ethylene-1-butene polymer component (A) and (ii) 50.0 to 65.0 wt% of ethylene-1-hexene polymer component (B).
[0055] Another preferred embodiment of the invention specifies that the total amount of 1-butene in the ethylene polymer component (A) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 0.5 to 5.0 wt%, preferably 0.6 to 4.0 wt%, more preferably 0.8 to 3.0 wt%, and even more preferably 1.0 to 2.0 wt%, based on the total weight of the ethylene polymer component (A).
[0056] In another preferred embodiment of the invention, the total amount of 1-hexene in the ethylene polymer component (B) of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is in the range of 3.0 to 25.0 wt%, preferably 4.0 to 22.0 wt%, more preferably 10 to 20.0 wt%, based on the total weight of the ethylene polymer component (B).
[0057] Multimodal copolymers (MMCPs) preferably have an MFR in the range of 22 to 60, more preferably 23 to 50, more preferably 25 to 48, and even more preferably 28 to 45. 21The ratio of (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO 1133), MFR 21 / MFR2.
[0058] Metallocene-catalyzed multimodal copolymers (MMCPs) are preferably (linear low-density) polyethylene (LLDPE), which has a well-known meaning.
[0059] More preferably, the multimodal copolymer (MMCP) is multimodal (i.e., there are differences between them) at least with respect to MFR2, the comonomer content is multimodal (i.e., there are differences between them) and the densities of the ethylene polymer components (A) and (B) are multimodal (i.e., there are differences between them), as defined above, below or in the claims, the claims covering any preferred range or embodiment of the polymer composition.
[0060] In addition, the multimodal copolymer (MMCP) may also have a molecular weight distribution (Mw / Mn) measured by GPC in the range of at least 3.5 to at most 7.2, preferably in the range of 4.0 to 7.0, and more preferably in the range of 4.5 to 6.8.
[0061] Within the scope of this invention, the first and second ethylene polymer portions (A-1 and A-2) of the ethylene polymer component (A) are present in a weight ratio of 4:1 to 1:4, for example 3:1 to 1:3, or 2:1 to 1:2, or 1:1.
[0062] The ethylene polymer component (A) is present in an amount of 35.0 to 50.0 wt% based on the multimodal copolymer (MMCP), preferably 36.0 to 48.0 wt%, and even more preferably 38.0 to 45.0 wt%.
[0063] Therefore, the ethylene polymer component (B) is present in an amount of 50.0 to 65.0 wt%, preferably 52.0 to 64.0 wt%, more preferably 55.0 to 62.0 wt%, based on the multimodal copolymer (MMCP).
[0064] Metallocene-catalyzed multimodal copolymers (MMCPs) can be produced in a two-stage process, preferably comprising a slurry reactor (loop reactor) connected in series with a gas phase reactor (GPR), thereby producing an ethylene polymer component (A) in the loop reactor and producing an ethylene polymer component (B) in the GPR in the presence of ethylene polymer component (A) to produce the multimodal copolymer (MMCP).
[0065] When the ethylene component (A) of a multimodal copolymer (MMCP) consists of ethylene polymer portions (A-1) and (A-2), the MMCP can be produced using a three-stage process. This process preferably includes a first slurry reactor (loop reactor 1), which is connected in series with another slurry reactor (loop reactor 2). The first ethylene polymer portion (A-1) produced in loop reactor 1 is fed into loop reactor 2, where a second ethylene polymer portion (A-2) is produced in the presence of the first portion (A-1). Loop reactor 2 is then connected in series with a gas-phase reactor (GPR), where the first ethylene polymer component (A) exiting the second slurry reactor is fed into the GPR to produce a trimodal polyethylene copolymer. In this case, the reaction conditions in the two slurry reactors are selected such that products with different MFRs and / or densities are produced in the two slurry reactors.
[0066] This method is described in particular in WO 2016 / 198273A1, WO 2021 / 009189A1, WO 2021 / 009190A1, WO2021 / 009191A1, and WO 2021 / 009192. Full details on how to prepare suitable metallocene-catalyzed multimodal copolymers (MMCPs) can be found in these references.
[0067] Metallocene-catalyzed multimodal copolymers (MMCPs) are produced using metallocene catalysts. These catalysts preferably comprise metallocene complexes and co-catalysts. The metallocene compounds or complexes are also referred to herein as organometallic compounds (C).
[0068] Organometallic compounds (C) contain transition metals (M) of elements in groups 3 to 10 of the periodic table (IUPAC 2007), or of the actinides or lanthanides.
[0069] According to the present invention, the term "organometallic compound (C)" includes any metallocene or nonmetallocene compound of transition metals, which has at least one organic (coordinating) ligand and exhibits catalytic activity alone or in combination with a co-catalyst. Transition metal compounds are well known in the art, and the present invention covers compounds of metals from Groups 3 to 10 of the periodic table (IUPAC 2007), such as Groups 3 to 7, or Groups 3 to 6, such as Groups 4 to 6, and lanthanides or actinides.
[0070] In one embodiment, the organometallic compound (C) has the following formula (I):
[0071]
[0072] Each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 -alkoxy, phenyl, or benzyl;
[0073] Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S;
[0074] L is -R'2Si-, where each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 - Hydrocarbon group or C 1-10 -alkyl;
[0075] M is Ti, Zr, or Hf;
[0076] Each R 1 Same or different, is C 1-6 -alkyl or C 1-6 -alkoxy group;
[0077] Each n is between 1 and 2;
[0078] Each R 2 Same or different, is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group;
[0079] Each R is arbitrarily selected by 1 to 3 Cs. 1-6 -alkyl-substituted C 1-10 -alkyl or phenyl; and
[0080] Each p is between 0 and 1.
[0081] Preferably, the compound of formula (I) has the following structure
[0082]
[0083] Each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 -alkoxy, phenyl, or benzyl;
[0084] L is Me2Si-;
[0085] Each R 1 Same or different and is C 1-6 -alkyl, such as methyl or tert-butyl;
[0086] Each n is between 1 and 2;
[0087] R 2 It is a -Si(R)3 alkyl group; each p is 1;
[0088] Each R is C 1-6-alkyl or phenyl.
[0089] The highly preferred formula (I) complex is
[0090]
[0091] Most preferably, the complex dimethylsilanediylbis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride is used.
[0092] More preferably, the ethylene polymer components (A) and (B) of the multimodal copolymer (MMCP) are prepared using the same metallocene catalyst, i.e., in the presence of the same metallocene catalyst.
[0093] To form the catalyst, a co-catalyst, also known as an activator, is used. Co-catalysts containing Al or B are well known and can be used here. Aluminoxanes (e.g., MAO) or boron-based co-catalysts (e.g., borates) are preferred.
[0094] In contrast to Ziegler-Natta catalysis, polyethylene copolymers prepared using single-point catalysis exhibit characteristics that distinguish them from Ziegler-Natta materials. In particular, the comonomer distribution is more uniform. This can be visualized using TREF or Crystaf techniques. Catalyst residues can also indicate the catalyst used. Ziegler-Natta catalysts do not contain, for example, Zr or Group IV (Hf) metals.
[0095] Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP)
[0096] The core layer (CL) of the multilayer film according to the invention comprises 60 to 95 wt% of a specific multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL). Other layers may also comprise the copolymer (ZNCP).
[0097] Multi-peak Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) exhibits a range of 925 to 950 kg / m³. 3 Density within the range (ASTM D792); and MFR5 (190°C, 5 kg, ISO 1133) within the range of 0.1 to 6.0 g / 10 min.
[0098] According to a preferred embodiment, the density (ASTM D792) of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) is between 920 and 950 kg / m³. 3 More preferably 927 to 947 kg / m 3 Even better is 930 to 945 kg / m 3 The optimal value is 930 to 943 kg / m³.3 Within the range.
[0099] According to a preferred embodiment of the invention, the multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) comprises (C) a low molecular weight (LMW) homopolymer of ethylene; and (D) a high molecular weight (HMW) terpolymer of ethylene, 1-butene, and 1-hexene. The LMW homopolymer portion (C) has a lower molecular weight than the HMW terpolymer portion (D).
[0100] The lower molecular weight fraction (C) of ZNCP has an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 200 to 1000 g / 10 min, preferably 250 to 800 g / 10 min, and an MFR2 in the range of 940 to 980 kg / m 3 Preferred weight is 945 to 975 kg / m³. 3 The density is within the range of ASTM D792, and the comonomer content is within the range of 0 to 2.5 mol%, preferably 0 to 2.0 mol%.
[0101] Compared to the lower molecular weight fraction (C), the higher molecular weight fraction (D) has a lower MFR2 and a lower density.
[0102] According to another preferred embodiment of the invention, the low molecular weight (LMW) homopolymer (C) of ethylene is composed of two homopolymer fractions (C-1) and (C-2), wherein the MFR2 (190°C, 2.16 kg, ISO 1133) of the homopolymer fraction (C-1) is preferably in the range of 100 to 400 g / 10 min, more preferably in the range of 150 to 300 g / 10 min and / or the MFR2 (190°C, 2.16 kg, ISO 1133) of the homopolymer fraction (C-2) is preferably in the range of 450 to 1200 g / 10 min, more preferably in the range of 600 to 1100 g / 10 min and / or the MFR2 of fraction (C-1) is preferably lower than the total MFR2 of the low molecular weight (LMW) homopolymer (C) of ethylene, and / or the densities of the two homopolymer fractions (C-1) and (C-2) may be the same or different and are in the range of 955 to 980 kg / m³. 3 Preferred weight is 965 to 980 kg / m³. 3 Or 965 to 975 kg / m 3 Within the range.
[0103] According to another preferred embodiment, the MFR5 (ISO 1133) of the multi-peaked Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) is in the range of 0.05 to 6.0 g / 10 min, more preferably in the range of 0.1 to 10 g / 10 min, and even more preferably in the range of 0.2 to 6.0 g / 10 min. The MFR5 (ISO 1133) is preferably in the range of 0.3 to 5.0 g / 10 min or 0.3 to 3.0 g / 10 min.
[0104] In another preferred embodiment of the invention, the MFR of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) is... 21 The range is 5.0 to 200 g / 10 min, preferably 10.0 to 200 g / 10 min, more preferably 10.0 to 100 g / 10 min, even more preferably 15.0 to 50.0 g / 10 min, and most preferably 15.0 g / 10 min to 45.0 g / 10 min.
[0105] The Mw of multi-peaked Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) can be in the range of 80,000 to 300,000, preferably in the range of 100,000 to 270,000, and more preferably in the range of 120,000 to 160,000.
[0106] Multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) is produced in the presence of Ziegler-Natta olefin polymerization catalysts. Ziegler-Natta catalysts are useful because they can produce polymers with a wide range of molecular weights and other desired properties at high productivity. The Ziegler-Natta catalysts used in this invention are preferably supported on an external support.
[0107] Suitable Ziegler-Natta catalysts preferably contain magnesium, aluminum, and titanium compounds supported on particulate supports. Particulate supports commonly used in Ziegler-Natta catalysts include inorganic oxide supports, such as those based on silica, alumina, titanium dioxide, silica-alumina, silica-titanium dioxide, or MgCl2.
[0108] The transition metal is preferably titanium. The titanium compound is a halogenated titanium compound, preferably a chlorine-containing titanium compound. A particularly preferred titanium compound is titanium tetrachloride.
[0109] As described in EP 0 688 794 A1 or WO 99 / 51646A1, the catalyst can be prepared by sequentially contacting the support with the above-described compound. Alternatively, preferably, it can be prepared by first preparing a solution from the components and then contacting the solution with the support, as described in WO 01 / 55230A1.
[0110] Ziegler-Natta catalysts are used in conjunction with activators, also known as co-catalysts. Suitable activators are metal alkyl compounds, typically Group 13 metal alkyl compounds, particularly alkylaluminum compounds. These include trialkylaluminum compounds such as trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, and tri-n-octylaluminum. Alkylaluminum compounds may also include alkylaluminum halides, such as ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum sesquichloride, dimethylaluminum chloride, etc., and alkylaluminum oxides, such as methylaluminoxane, hexaisobutylaluminoxane, and tetraisobutylaluminoxane, as well as other alkylaluminum compounds, such as isoprenylaluminium. Particularly preferred co-catalysts are trialkylaluminum, with triethylaluminum, trimethylaluminum, and triisobutylaluminum being particularly preferred.
[0111] The amount of activator used depends on the specific catalyst and activator. Typically, triethylaluminum is used in such an amount that the molar ratio of aluminum to transition metal (such as Al / Ti) is, for example, 1 to 1000, preferably 3 to 100, particularly about 5 to about 30 mol / mol.
[0112] Multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) can be produced by polymerization using conditions that produce multimodal (e.g., bimodal) polymers. Typically, two or more stages are used, i.e., a multi-stage polymerization process, with different process conditions (e.g., different temperatures, pressures, polymerization media, hydrogen partial pressures, etc.) in different stages or regions. Preferably, the multimodal (e.g., bimodal) polymer is produced by multi-stage polymerization, for example using a series of reactors, with the optional comonomer preferably added only in the reactor used to produce the higher / highest molecular weight component. A multi-stage method is defined as a polymerization method in which a polymer comprising two or more fractions is produced by producing each or at least two polymer fractions in separate reaction stages (typically with different reaction conditions in each stage) in the presence of the reaction products of a preceding stage containing a polymerization catalyst. The polymerization reaction used in each stage can involve conventional ethylene homopolymerization or copolymerization using conventional reactors (e.g., loop reactors, gas-phase reactors, batch reactors, etc.), such as gas-phase, slurry, or liquid-phase polymerization (see, for example, WO97 / 44371A1 and WO96 / 18662A1). Polymers that meet the requirements of this invention are known and can be purchased from suppliers such as Borealis and Borouge, for example, FX1001.
[0113] Multilayer film
[0114] According to a preferred embodiment of the multilayer film of the present invention, the core layer (CL) comprises, preferably, the following components: (a) 10 to 25 wt%, preferably 18 to 22 wt%, of metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL) and (b) 75 to 90 wt%, preferably 78 to 82 wt%, of multimodal Ziegler-Natta-catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL); wherein components (a) and (b) together comprise at most 100 wt%.
[0115] According to another preferred embodiment of the invention, the multilayer film comprises a surface layer (SKL), a core layer (CL), and a sealing layer (SL). It goes without saying that the core layer (CL) is located between the surface layer (SKL) and the sealing layer (SL).
[0116] According to another preferred embodiment of the invention, the surface layer (SKL) comprises, preferably consists of, the following components: 80 to 95 wt%, more preferably 82 to 93 wt%, and even more preferably 88 to 92 wt% of metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the surface layer (SKL); and 5 to 20 wt%, preferably 7 to 18 wt%, more preferably 8 to 12 wt% of LDPE based on the total weight of the surface layer (SKL), wherein the density (ASTM D792) of the LDPE is 920 to 940 kg / m³. 3 Preferred weight is 930 to 936 kg / m³. 3 Within the range of 0.5 to 4.0 g / 10 min, preferably 0.1 to 1.0 g / 10 min, MFR2 (190°C, 2.16 kg, ISO 1133) is present.
[0117] According to a preferred embodiment of the multilayer film of the present invention, the sealing layer (SL) comprises, preferably consists of, the following components: 90 to 100 wt%, preferably 95 to 100 wt%, of a metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the sealing layer (SL), or 50 to 70 wt%, preferably 55 to 65 wt%, of a plastic body based on the total weight of the sealing layer (SL), wherein the plastic body is preferably a copolymer of ethylene and 1-octene, preferably having a content of 860 to 910 kg / m³. 3 The preferred strength is 895 to 905 kg / m³. 3The density is within the range of ASTM D792 and the MFR2 (190°C, 2.16 kg, ISO 1133) is within the range of 0.5 to 10.0 g / 10 min, preferably 1.0 to 1.5 g / 10 min; and the content of MFR2 is within the range of 0.5 to 10.0 g / 10 min, preferably 1.0 to 1.5 g / 10 min; and the content of MFR2 is within the range of 1.5 to 10.0 g / 10 min, preferably 1.0 to 1.5 g / 10 min. The total weight of the sealing layer (SL) is 30 to 50 wt%, preferably 35 to 45 wt%, of multimodal metallocene-catalyzed linear low-density polyethylene, preferably a bimodal ethylene / 1-butene / 1-hexene terpolymer, preferably having a density of 910 to 930 kg / m³. 3 More preferably 916 to 925 kg / m 3 Density within the range (ASTM D792); and MFR2 (190°C, 2.16 kg, ISO 1133) within the range of 0.5 to 2.0 g / 10 min.
[0118] The polymers used in the multilayer films according to the present invention may contain additives and fillers in amounts conventional in membrane applications. Examples of such additives include, in particular, antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers, and polymer processing aids (PPAs).
[0119] It should be understood in this document that any additives and / or fillers may optionally be added in the form of a so-called masterbatch, which comprises the corresponding (multiple) additives and a carrier polymer. In this case, based on the total amount (100 wt%) of the polymer composition, the carrier polymer is not calculated in the polymer component of the metallocene-catalyzed multimodal polyethylene copolymer (MMCP), but rather in the amount of the corresponding additive.
[0120] According to another preferred embodiment of the invention, the thickness of the surface layer (SKL) of the multilayer film is in the range of 1 to 100 μm, preferably in the range of 5 to 80 μm, and more preferably in the range of 10 to 15 μm.
[0121] According to another preferred embodiment of the invention, the core layer (CL) of the multilayer film has a thickness in the range of 10 to 200 μm, preferably in the range of 20 to 80 μm, and more preferably in the range of 30 to 45 μm.
[0122] In another preferred embodiment of the multilayer film according to the invention, the thickness of the sealing layer (SL) of the multilayer film is in the range of 1 to 50 μm, preferably in the range of 5 to 25 μm, and more preferably in the range of 10 to 15 μm.
[0123] According to another preferred embodiment of the invention, the thickness of the multilayer film is in the range of 12 to 350 μm, preferably in the range of 40 to 150 μm, and more preferably in the range of 50 to 90 μm.
[0124] According to another preferred embodiment of the invention, the multilayer film has a longitudinal tensile modulus (ISO 527-3) in the range of 200 to 500 MPa, preferably in the range of 280 to 400 MPa.
[0125] In another preferred embodiment of the multilayer film according to the invention, the transverse tensile modulus (ISO527-3) of the multilayer film is in the range of 250 to 600 MPa, preferably in the range of 340 to 500 MPa.
[0126] According to another preferred embodiment of the invention, the dart strength (ISO 7765-1) of the multilayer film is in the range of 500 to 1000 g, preferably in the range of 800 to 950 g.
[0127] In another preferred embodiment of the multilayer film according to the invention, the multilayer film has a sealing initiation temperature determined as described in the specification, in the range of 60 to 85°C, preferably in the range of 63 to 68°C.
[0128] According to another preferred embodiment of the invention, the multilayer film is composed of a polyethylene-based polymer.
[0129] method
[0130] Another aspect of the present invention relates to a method for producing multilayer films.
[0131] The multilayer film according to the present invention is typically prepared by conventional methods, wherein the layers of the film are co-extruded.
[0132] The different polymer components in any layer of the film are typically tightly mixed before layer formation, for example using a twin-screw extruder, preferably a counter-rotating or co-rotating extruder. The blend is then converted into a co-extruded film.
[0133] Generally, the multilayer film according to the present invention can be produced by blown film or cast film process, preferably by blown film process.
[0134] To manufacture such a film, at least three polymer melt streams are simultaneously extruded (i.e., co-extruded) through a multi-channel tubular, annular, or circular die to form a tube, which is then inflated, expanded, and / or cooled with air to form a film. The manufacture of blown films is a well-known process.
[0135] Blow molding (co)extrusion can be carried out at a temperature of 150 to 230°C, more preferably 160 to 225°C, and cooled by blowing gas (usually air) at a temperature of 10 to 40°C, more preferably 12 to 16°C, to provide a frosting height of 0.5 to 4 times, more preferably 1 to 2 times, the mold diameter.
[0136] The blow-up ratio (BUR) should generally be in the range of 1.5 to 3.5, preferably 2.0 to 3.0, and more preferably 2.1 to 2.8.
[0137] use
[0138] Another aspect of the invention refers to the use of the multilayer film as a packaging material, which is preferably used for food and / or medical products.
[0139] The invention will now be described with reference to the following non-limiting embodiments.
[0140] Experimental Section
[0141] A. Testing Methods
[0142] Unless otherwise defined, the following terms and measurement methods apply to the above general description of the invention and the following embodiments.
[0143] melt flow rate
[0144] According to ISO 1133 - Determination of melt flow rate (MFR) and melt volumetric flow rate (MVR) of thermoplastics - Part 1: Standard methods, melt flow rate (MFR) is determined and expressed in g / 10 min. MFR is an indicator of the polymer's flowability and therefore its processability. A higher melt flow rate generally indicates a lower polymer viscosity. The MFR of polyethylene is determined at 190°C. MFR can be determined under different loads, such as 2.16 kg (MFR2), 5 kg (MFR5), or 21.6 kg (MFR6). 21 ).
[0145] Calculation of MFR2 for component B and part (A-2)
[0146] logA = x·logB + (1-x)·logC
[0147]
[0148] For component B:
[0149] B = MFR2 of component (A)
[0150] C = MFR2 of component (B)
[0151] A = Final MFR2 (mixture) of multimodal polyethylene copolymer (P)
[0152] X = weight fraction of component (A)
[0153] For part (A-2):
[0154] B = MFR2 of Part 1 (A-1)
[0155] C = MFR2 of Part 2 (A-2)
[0156] A = The final MFR2 (mixture) of the cyclic polymer (= component (A))
[0157] X = the weight fraction of part 1 (A-1).
[0158] density
[0159] According to ASTM D792, Method B (density determination by balance at 23°C), the density of the polymer is measured on a compression-molded specimen prepared according to EN ISO 1872-2, in kg / m³. 3 .
[0160] DSC analysis, melting temperature (T) m ) and crystallization temperature (T) c )
[0161] Data can be measured on samples of 5 to 7 mg using the TA Instrument Q2000 Differential Scanning Calorimetry (DSC). DSC should be run in hot / cold / hot cycling at a scan rate of 10 °C / min over a temperature range of -30 to +225 °C, according to ISO 11357 / Part 3 / Method C2.
[0162] Crystallization temperature (T) c ) and crystallization enthalpy (H c The melting temperature (T) is determined by the cooling step, while the melting temperature (T) is determined by the cooling step. m ) and enthalpy of fusion (H m The result is determined by the second heating step.
[0163] Dart Drop Strength (DDI): A measure of impact resistance using the free-fall dart method.
[0164] According to ISO 7765-1:1988 / Method A, the DDI (Damage Disruption Intake) is measured for membranes produced as shown below. This test method covers the determination of the energy leading to membrane failure under specified conditions of impact from a dart dropped freely from a specified height, which will cause 50% of the test samples to fail (Step Method A). A uniform mass increment of the missile is used throughout the test, and after each test, the missile weight is reduced or increased by the uniform increment based on the observed result (failure or no failure) of the sample.
[0165] Standard conditions:
[0166] Adjustment time: >96h
[0167] Test temperature: 23℃
[0168] Darthead material: phenolic resin
[0169] Dart diameter: 38mm
[0170] Drop height: 660mm
[0171] result:
[0172] Impact damage weight -50% [g].
[0173] Tensile modulus (TM)
[0174] The tensile modulus (MPa) of the membrane sample (prepared as described below) was measured in the longitudinal (MD) and / or transverse (TD) directions according to ISO 527-3, with a membrane thickness of 60 μm and a crosshead speed of 1 mm / min. Seal initiation temperature (SIT); seal termination temperature (SET); seal range.
[0175] This method determines the sealing temperature range (sealing range) of polyethylene films, particularly blown or cast films. The sealing temperature range is the temperature range within which the film can be sealed under the conditions given below.
[0176] The lower limit (heat seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of ≥5N is achieved. The upper limit (seal end temperature (SET)) is reached when the membrane adheres to the sealing device.
[0177] Measurements were performed according to a slightly modified version of ASTM F1921-12, in which the test parameters of sealing pressure, delay time, and clamp separation rate were modified. The force / temperature profile was continued until the membrane underwent thermal failure.
[0178] The sealing range was determined on a 60 μm thick blown film (blown film) produced as described below using a J&B General Seal Machine Model 4000, with the following additional parameters used:
[0179] Adjustment time: >96h
[0180] Sample width: 25mm
[0181] Sealing pressure: 0.4 N / mm 2 (PE)
[0182] Sealing time: 1 second
[0183] Delay time: 30 seconds
[0184] Jaws (sealing clamps) size: 50x5 mm
[0185] Sealing clamp shape: flat
[0186] Sealing clamp coating: Niptef
[0187] Sealing temperature: ambient temperature -240℃
[0188] Sealing temperature interval: 5℃
[0189] Starting temperature: 50℃
[0190] Grip separation rate: 42 mm / s
[0191] Comonomer content - Quantitative analysis of microstructure using NMR spectroscopy
[0192] Quantitative nuclear magnetic resonance (NMR) spectroscopy is used to quantify the comonomer content of the polymer.
[0193] Using a Bruker Avance III 400MHz NMR spectrometer, respectively for 1 H and 13 C was operated at 500.13 and 125.76 MHz, and quantitative measurements were recorded in the molten state. 13 C{ 1 HNMR spectroscopy. All spectra are performed using... 13 Recordings were performed using a C-optimized 7mm magic angle rotation (MAS) probe at 150°C, with all pneumatic devices using nitrogen. Approximately 200 mg of material was loaded into a 7mm outer diameter zirconia MAS rotor and rotated at 4 kHz. This setup was chosen primarily for the high sensitivity required for rapid identification and accurate quantification. Standard single-pulse excitation was employed, utilizing NOE with a 3-second short cyclic delay and an RS-HEPT decoupling scheme. A total of 1024 (1k) transients were obtained for each spectrum.
[0194] Quantitative 13 C{ 1 The ¹H NMR spectra were processed, integrated, and the relevant quantitative characteristics were determined by integration. All chemical shifts were internally referenced to the bulk methylene signal (δ+) at 30.00 ppm.
[0195] The amount of ethylene was quantified by integrating the methylene (δ+) sites at 30.00 ppm and taking into account the number of reporter sites for each monomer:
[0196] E = I δ+ / 2
[0197] The presence of separate comonomer units is corrected based on the number of existing separate comonomer units:
[0198] E total = E + (3 *B+2 * H) / 2
[0199] B and H are defined for their respective comonomers. Corrections are made in a similar manner when continuous and discontinuous comonomers are incorporated.
[0200] Observing the characteristic signal corresponding to the incorporation of 1-butene, the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:
[0201] fB total = (B total / (E total + B total + H total))
[0202] Use at 39.8 ppm * The amount of isolated 1-butene incorporated into the EEBEE sequence is quantified by integrating the B2 site and considering the number of reporter sites for each comonomer:
[0203] B = I *B2
[0204] If present, the amount of sequentially incorporated 1-butene in the EEBBEE sequence is quantified by integrating the ααB2B2 site at 39.4 ppm and taking into account the number of reporter sites for each comonomer:
[0205] BB=2 * IααB2B2
[0206] If present, the amount of non-reporter sites per comonomer:
[0207] HEH=2 * IββB4B4
[0208] No HHH sequence was observed. The total 1-hexene content was calculated based on the sum of isolated, continuous, and discontinuous incorporations:
[0209] H total = H + HH + HEH
[0210] The total mole fraction of 1-hexene in the polymer was then calculated as follows:
[0211] fH = H total / (E total + B total + H total)
[0212] The molar percentage of comonomer incorporated is calculated from the mole fraction:
[0213] B[mol%] = 100 * fB
[0214] H[mol%] = 100 * fH
[0215] The weight percentage of comonomer incorporated is calculated as a mole fraction:
[0216] B[wt%] = 100 * (fB * 56.11) / ((fB * 56.11)+(fH * 84.16)+((1-(fB+fH)) * 28.05))
[0217] H[wt%] = 100 * (fH * 84.16) / ((fB * 56.11)+(fH * 84.16)+((1-(fB+fH)) * 28.05))
[0218] References:
[0219] Klimke,K.,Parkinson,M.,Piel,C.,Kaminsky,W.,Spiess,H.W.,Wilhelm,M.,Macromol.Chem.Phys.2006;207:382.
[0220] Parkinson,M.,Klimke,K.,Spiess,H.W.,Wilhelm,M.,Macromol.Chem.Phys.2007;208:2128.
[0221] Pollard,M.,Klimke,K.,Graf,R.,Spiess,H.W.,Wilhelm,M.,Sperber,O.,Piel,C.,Kaminsky,W.,Macromolecules 2004;37:813.
[0222] Filip,X.,Tripon,C.,Filip,C.,J.Mag.Resn.2005,176,239.
[0223] Griffin,J.M.,Tripon,C.,Samoson,A.,Filip,C.,and Brown,S.P.,Mag.Res.inChem.2007 45,S1,S198.
[0224] Castignolles,P.,Graf,R.,Parkinson,M.,Wilhelm,M.,Gaborieau,M.,Polymer50(2009)2373.
[0225] Busico,V.,Cipullo,R.,Prog.Polym.Sci.26(2001)443.
[0226] Busico,V.,Cipullo,R.,Monaco,G.,Vacatello,M.,Segre,AL,Macromoleucles30(1997)6251.
[0227] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225.
[0228] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128.
[0229] Resconi,L.,Cavallo,L.,Fait,A.,Pimontesi,F.,Chem.Rev.2000,100,1253.
[0230] B. Materials used
[0231] FT5236 is a low-density polyethylene (MFR2 (190℃ / 2.16kg): 0.75g / 10min, density: 923kg / m³) available from Borealis AG. 3 T m 112℃ (manufactured by Tubular Technology) and contains anti-blocking agents, antioxidants and slip additives.
[0232] FK1820 is a type of device that can be sourced from Borouge and Anteo. TM The bimodal ethylene / 1-butene / 1-hexene terpolymer (MFR2 (190℃ / 2.16kg): 1.5g / 10min, density: 918kg / m³) purchased from FK1820 3 T m It is produced at 122°C using a metallocene catalyst and contains antioxidants and processing aids.
[0233] The FX1001 is a product that can be obtained from Borealis AG using BorShape. TM The multimodal α-olefin terpolymer (MFR5 (190℃ / 5kg)) purchased from FX1001: 0.9g / 10min, MFR 21 (190℃ / 21kg: 20.0g / 10min, density: 931kg / m³) 3 T m The product is manufactured at 127°C with a C4 content of 2.2 wt% and a C6 content of 4.0 wt% based on the total weight of the polymer (produced using Ziegler-Natta catalyst ZNCP) and contains antioxidants.
[0234] Queo 0201 is a product available from Borealis AG via Queo. TM The monophasic ethylene-based 1-octene plastide (MFR2 (190℃ / 2.16kg)) purchased from 0201 has a density of 902kg / m³ and a concentration of 1.1g / 10min. 3 T m It is produced at 97°C using a metallocene catalyst in solution polymerization and contains processing stabilizers.
[0235] ZNCP is a multimodal α-olefin terpolymer (MFR5 (190℃ / 5kg): 1.5g / 10min, MFR 21 (190℃ / 21kg: 32.0g / 10min, density: 941kg / m³) 3 T m 128°C, with a C4 content of 0.9 wt% and a C6 content of 3.1 wt% based on the total weight of the polymer, produced using a Ziegler-Natta catalyst and produced as follows.
[0236] Polymerization was carried out in a Borstar pilot plant with a three-reactor configuration (loop 1-loop 2-GPR) and a prepolymerization loop reactor, according to the conditions given in Table 1. The solid polymerization catalyst component prepared according to Example 1 of EP 1 378 528 A1 was introduced into the reactor along with a triethylaluminum cocatalyst, such that the Al / Ti molar ratio was approximately 15.
[0237] Table 1: Aggregation conditions:
[0238] Temperature (°C) 70 Pressure (kPa) 5783 Divided into (wt%) 2 First loop reactor Temperature (°C) 95 Pressure (kPa) 5512 C2 (mol%) 4.7 H2 / C2 (mol / kmol) 306 MFR2 (g / 10min) 195 Divided into (wt%) 18 Second loop reactor Temperature (°C) 95 Pressure (kPa) 5382 C2 (mol%) 5.5 H2 / C2 (mol / kmol) 563 Divided into (wt%) 26 <![CDATA[MFR2(g / 10min)]]> 390 gas phase reactor Temperature (°C) 82 Pressure (kPa) 1988 C2 (mol%) 13.1 H2 / C2 (mol / kmol) 22.0 C4 / C2 (mol / kmol) 94.4 C6 / C2 (mol / kmol) 123.5 Divided into (wt%) 54
[0239] Under a nitrogen atmosphere, the polymer powder was mixed with 1200 ppm Irganox B561 (purchased from BASF SE) and 400 ppm calcium stearate. The mixture was then compounded and extruded into granules using a JSW CIMP90 twin-screw extruder under a nitrogen atmosphere.
[0240] MMCP1, MMCP2, and MMCP3 are multimodal copolymers and are prepared as follows:
[0241] Catalyst preparation (CAT)
[0242] SiO2 loading:
[0243] Add 10 kg of silica (PQ Corporation ES757, calcined at 600°C) from the feed hopper and inertize it in the reactor until the O2 level is below 2 ppm.
[0244] Preparation of MAO / tol / MC:
[0245] A 30 wt% MAO toluene solution (14.1 kg) was added from a balance to another reactor under stirring at 25 °C (oil circulation temperature) and 95 rpm, followed by the addition of toluene (4.0 kg). After the addition of toluene, the stirring speed was increased from 95 rpm to >200 rpm for 30 minutes. 477 g of metallocene racemic-dimethylsilanediylbis{2-(5-(trimethylsilyl)furan-2-yl)-4,5-dimethylcyclopentadien-1-yl}zirconium dichloride was added from a metal cylinder, followed by rinsing with 4 kg of toluene (total toluene 8.0 kg). The reactor stirring speed was changed to 95 rpm for MC feed, then returned to 200 rpm and maintained for 3 hours. After the reaction time, the MAO / tol / MC solution was transferred to a feed vessel.
[0246] Catalyst preparation:
[0247] The reactor temperature was set to 10°C (oil circulation temperature), and the stirring was adjusted to 40 rpm during the addition of MAO / tol / MC. The MAO / tol / MC solution (22.2 kg) was added over 205 minutes, followed by stirring for 60 minutes (oil circulation temperature set to 25°C). After stirring, the "dry mixture" was stabilized at 25°C (oil circulation temperature) for 12 hours with a stirring speed of 0 rpm. The reactor was rotated 20° (back and forth) and stirred several times per hour at a speed of 5 rpm.
[0248] After stabilization, the catalyst was dried at 60°C (oil circulation temperature) for 2 hours under a nitrogen flow of 2 kg / h, followed by vacuum drying for 13 hours (with the same nitrogen flow rate and stirring at 5 rpm). Samples of the dried catalyst were taken, and the HC content was measured using thermogravimetric analysis with a Sartorius moisture analyzer (model MA45) in a glove box. The target HC level was <2% (actual 1.3%).
[0249] polymerization:
[0250] Polymerization was carried out in the Borstar pilot plant with a 3-reactor unit (loop 1-loop 2-GPR) and a prepolymerization loop reactor, according to the conditions given in Table 2.
[0251] Table 2: Aggregation conditions.
[0252]
[0253]
[0254] The polymer (MMCP1-3) was mixed with 2400 ppm of Irganox B561 (available from BASF SE) and 270 ppm of Dynamar FX 5922 (available from 3M), compounded and extruded into granules using a JSW extruder under a nitrogen atmosphere, resulting in an SEI of 230 kWh / kg and a melt temperature of 250 °C. Table 3 summarizes some properties of MMCP1-3 and FK1820.
[0255] Table 3: Characteristics of multimodal copolymers.
[0256]
[0257]
[0258] C. Manufacturing of the three-layer membrane
[0259] A three-layer film with a total thickness of 60 μm and the composition shown in Table 4 was produced on the Collin 3-layer laboratory production line (BUR = 1:2.5, winding speed = 7 m / min, melt temperature = 210 °C).
[0260] D. Result
[0261] Table 4: Composition and properties of the three-layer membrane.
[0262]
[0263] wt%, based on the total weight of the three-layer membrane.
[0264] E. Discussion of the results
[0265] The produced membrane has a core layer made of a specific blend of metallocene-catalyzed multimodal polyethylene copolymer (MMCP) and multimodal Ziegler-Natta-catalyzed linear low-density polyethylene (ZNCP). The MMCP used in the membrane according to the invention has an MFR in the range of 22 to 70. 21 The ratio of MFR2 (190℃, 21.6kg, ISO 1133) to MFR3 (190℃, 2.16kg, ISO 1133) 21 / MFR2. Due to the same sealing layer, the membrane according to IE1 is comparable to the membranes of CE1 and CE2. As can be seen from Table 4 above, the membrane according to the invention has an excellent impact resistance / stiffness ratio. Furthermore, the membrane according to the invention has an improved balance between mechanical properties and sealing performance (see TM(MD)*DDI / SIT, which is 2523 relative to 1798 and 2369). The membrane according to IE2 is comparable to the membrane according to CE3 and exhibits not only improved impact resistance as expressed by dart impact strength but also improved sealing performance as expressed by seal initiation temperature (see also TM(MD)*DDI / SIT, which is 4014 relative to 2951). The choice of material in the core layer significantly affects the performance of the multilayer membrane.
Claims
1. A multilayer membrane comprising a surface layer (SKL), a core layer (CL), and a sealing layer (SL); wherein The core layer (CL) includes (a) 5 to 40 wt% of a metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL), which has Between 880 and 925 kg / m 3 Density within the range measured according to ASTM D792; MFR2 measured at 190°C under a load of 2.16 kg, according to ISO 1133, in the range of 0.1 to 6.0 g / 10 min; and MFR measured at 190°C under a load of 21.6 kg according to the method of ISO 1133 in the range of 22 to 70. 21 The ratio of MFR2 to the MFR measured at 190°C under a load of 2.16 kg according to ISO 1133 method, MFR 21 / MFR2; and (b) 60 to 95 wt% of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL), which has Between 925 and 950 kg / m 3 Density within the range measured according to ASTM D792; and MFR5 measured at 190°C under a 5 kg load according to ISO 1133 in the range of 0.1 to 6.0 g / 10 min; where The sum of the amounts of components (a) and (b) is at most 100 wt%.
2. The multilayer film according to claim 1, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has the following composition: Ethylene polymer component A; and Ethylene polymer component B.
3. The multilayer film according to claim 2, characterized in that, The ethylene polymer component A is a copolymer of ethylene and 1-butene.
4. The multilayer film according to claim 3, characterized in that, The total amount of 1-butene based on MMCP ranges from 0.1 to 1.5 wt%.
5. The multilayer film according to claim 3, characterized in that, The total amount of 1-butene based on MMCP ranges from 0.2 to 1.3 wt%.
6. The multilayer film according to claim 3, characterized in that, The total amount of 1-butene based on MMCP ranges from 0.4 to 1.2 wt%.
7. The multilayer film according to claim 3, characterized in that, The total amount of 1-butene based on MMCP is in the range of 0.4 to 0.6 wt%.
8. The multilayer film according to claim 2, characterized in that, The ethylene polymer component A consists of ethylene polymer portion A-1 and ethylene polymer portion A-2.
9. The multilayer film according to claim 2, characterized in that, The ethylene polymer component B is a copolymer of ethylene and 1-hexene.
10. The multilayer film according to claim 9, characterized in that, The total amount of 1-hexene based on MMCP ranges from 2.0 to 20.0 wt%.
11. The multilayer film according to claim 9, characterized in that, The total amount of 1-hexene based on MMCP ranges from 4.0 to 18.0 wt%.
12. The multilayer film according to claim 9, characterized in that, The total amount of 1-hexene based on MMCP ranges from 6.0 to 15.0 wt%.
13. The multilayer film according to claim 2, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has The total amount of 1-butene in ethylene polymer component A, ranging from 0.5 to 5.0 wt% based on the total weight of ethylene polymer component A; and / or The total amount of 1-hexene in ethylene polymer component B, ranging from 3.0 to 25.0 wt% based on the total weight of ethylene polymer component B; and / or The MFR2 of ethylene polymer fraction A-1 in the range of 1.0 to 15.0 g / 10 min or 100 to 140 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133; and / or The MFR2 of ethylene polymer fraction A-2 in the range of 2.0 to 30.0 g / 10 min or 100 to 140 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133; and / or The MFR2 of ethylene polymer component A in the range of 2.0 to 30.0 g / 10 min or 100 to 140 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133; and / or The MFR2 of ethylene polymer fraction B in the range of 0.001 to 1.5 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133, and / or The ratio of MFR2 of ethylene polymer component A in the range of 2.5 to 20.0, measured at 190°C under a load of 2.16 kg according to ISO 1133, to the MFR2 of MMCP, measured at 190°C under a load of 2.16 kg according to ISO 1133.
14. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a total amount of 1-butene in ethylene polymer component A ranging from 0.6 to 4.0 wt% based on the total weight of ethylene polymer component A.
15. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a total amount of 1-butene in ethylene polymer component A ranging from 0.8 to 3.0 wt% based on the total weight of ethylene polymer component A.
16. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a total amount of 1-butene in ethylene polymer component A in the range of 1.0 to 2.0 wt% based on the total weight of ethylene polymer component A.
17. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a total amount of 1-hexene in ethylene polymer component B ranging from 4.0 to 22.0 wt% based on the total weight of ethylene polymer component B.
18. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a total amount of 1-hexene in ethylene polymer component B in the range of 10.0 to 20.0 wt% based on the total weight of ethylene polymer component B.
19. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction A-1 in the range of 1.5 to 13.0 g / 10 min or 110 to 130 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
20. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction A-1 in the range of 2.0 to 11.0 g / 10 min or 115 to 125 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
21. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction A-1 in the range of 2.0 to 10.5 g / 10 min or 117 to 124 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
22. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction A-2 in the range of 2.5 to 20.0 g / 10 min or 110 to 130 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
23. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction A-2 in the range of 3.0 to 15.0 g / 10 min or 115 to 125 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
24. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer component A in the range of 2.5 to 20.0 g / 10 min or 110 to 130 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
25. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer component A in the range of 3.0 to 15.0 g / 10 min or 115 to 128 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
26. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer component A in the range of 3.2 to 10.0 g / 10 min or 120 to 125 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
27. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction B in the range of 0.01 to 1.5 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
28. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer MMCP has an MFR2 of ethylene polymer fraction B in the range of 0.05 to 1.2 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
29. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction B in the range of 0.1 to 1.0 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
30. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 of ethylene polymer fraction B in the range of 0.2 to 0.7 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
31. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 ratio of ethylene polymer component A, measured at 190°C under a 2.16 kg load according to ISO 1133, in the range of 3.0 to 15.0, to the MFR2 of MMCP, measured at 190°C under a 2.16 kg load according to ISO 1133.
32. The multilayer film according to claim 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has an MFR2 ratio of ethylene polymer component A, measured at 190°C under a 2.16 kg load according to ISO 1133, in the range of 3.5 to 10.0, to the MFR2 of MMCP, measured at 190°C under a 2.16 kg load according to ISO 1133.
33. The multilayer film according to claim 2 or 13, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has Between 920 and 950 kg / m 3 The density of ethylene polymer component A within the range, as measured according to ASTM D792; and / or Between 880 and 915 kg / m 3 The density of ethylene polymer component B within the range, as measured according to ASTM D792; and / or Between 920 and 960 kg / m 3 The density of polymer fraction A-1 within the range, as measured according to ASTM D792; and / or Between 930 and 950 kg / m 3 The density of polymer fraction A-2 within the range, as measured according to ASTM D792; and / or The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) itself has a density of 900 to 925 kg / m³ as measured according to ASTM D792. 3 Within the range.
34. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 925 to 950 kg / m³. 3 The density of ethylene polymer component A within the range, as measured according to ASTM D792.
35. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 930 to 945 kg / m³. 3 The density of ethylene polymer component A within the range, as measured according to ASTM D792.
36. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 885 to 910 kg / m³. 3 The density of ethylene polymer component B within the range, as measured according to ASTM D792.
37. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 890 to 905 kg / m³. 3 The density of ethylene polymer component B within the range, as measured according to ASTM D792.
38. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 925 to 955 kg / m³. 3 The density of polymer fraction A-1 within the range, as measured according to ASTM D792.
39. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 930 to 950 kg / m³. 3 The density of polymer fraction A-1 within the range, as measured according to ASTM D792.
40. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) has a concentration of 935 to 945 kg / m³. 3 The density of polymer fraction A-2 within the range, as measured according to ASTM D792.
41. The multilayer film according to claim 33, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) itself has a density of 910 to 925 kg / m³ as measured according to ASTM D792. 3 Within the range.
42. The multilayer film according to claim 1, characterized in that, The metallocene-catalyzed multimodal polyethylene copolymer (MMCP) is produced in the presence of the metallocene complex of formula (I): (I) Each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 -alkoxy, phenyl, or benzyl; Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S; L is -R'2Si-, where each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 - Hydrocarbon group or C 1-10 -alkyl; M is Ti, Zr, or Hf; Whether each R1 is the same or different is C 1-6 -alkyl or C 1-6 -alkoxy group; Each n is between 1 and 2; Whether each R2 is the same or different is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group; Each R is arbitrarily selected by 1 to 3 Cs. 1-6 -alkyl-substituted C 1-10 -alkyl or phenyl; and Each p is between 0 and 1.
43. The multilayer film according to claim 1, characterized in that, The multi-peaked Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) contains (C) Low molecular weight (LMW) homopolymers of ethylene; and (D) A high molecular weight (HMW) terpolymer of ethylene, 1-butene, and 1-hexene; wherein The molecular weight of the LMW homopolymer portion (C) is lower than that of the HMW terpolymer portion (D). The lower molecular weight fraction (C) of ZNCP has i) MFR2 measured at 190°C under a load of 2.16 kg according to the method of ISO 1133 in the range of 200 to 1000 g / 10 min; ii) At 940 to 980 kg / m 3 Density within the range measured according to ASTM D792; and iii) The comonomer content in the range of 0 to 2.5 mol%; and Compared to the lower molecular weight fraction (C), the higher molecular weight fraction (D) has a lower MFR2 and a lower density.
44. The multilayer film according to claim 43, characterized in that, The lower molecular weight fraction (C) of ZNCP has an MFR2 in the range of 250 to 800 g / 10 min, measured at 190 °C under a load of 2.16 kg according to the method of ISO 1133.
45. The multilayer film according to claim 43, characterized in that, The lower molecular weight fraction (C) of ZNCP has a concentration of 945 to 975 kg / m³. 3 Density within the range measured according to ASTM D792.
46. The multilayer film according to claim 43, characterized in that, The lower molecular weight fraction (C) of ZNCP has a comonomer content in the range of 0 to 2.0 mol%.
47. The multilayer film according to claim 43, characterized in that, The lower molecular weight (LMW) homopolymer (C) of the ethylene is composed of two homopolymer moieties, C-1 and C-2; in The MFR2 of homopolymer C-1, measured according to ISO 1133 at 190°C under a load of 2.16 kg, is in the range of 100 to 400 g / 10 min; and / or The MFR2 of homopolymer C-2, measured according to ISO 1133 at 190°C under a load of 2.16 kg, is in the range of 450 to 1200 g / 10 min; and / or The MFR2 of C-1 is lower than the total MFR2 of the lower molecular weight (LMW) homopolymer (C) of the ethylene, and / or The densities of the two homopolymer fractions C-1 and C-2 may be the same or different and range from 955 to 980 kg / m³. 3 Within the range.
48. The multilayer film according to claim 47, characterized in that, The MFR2 of homopolymer C-1, measured at 190°C under a load of 2.16 kg according to ISO 1133, was in the range of 150 to 300 g / 10 min.
49. The multilayer film according to claim 47, characterized in that, The MFR2 of homopolymer C-2, measured at 190°C under a load of 2.16 kg according to ISO 1133, was in the range of 600 to 1100 g / 10 min.
50. The multilayer film according to claim 47, characterized in that, The densities of the two homopolymer fractions, C-1 and C-2, are between 965 and 980 kg / m³. 3 Within the range.
51. The multilayer film according to claim 47, characterized in that, The densities of the two homopolymer fractions, C-1 and C-2, are between 965 and 975 kg / m³. 3 Within the range.
52. The multilayer film according to claim 1, characterized in that, The core layer (CL) comprises, or is composed of, the following: (a) 10 to 25 wt% of metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL); and (b) 75 to 90 wt% of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL); wherein The sum of the amounts of components (a) and (b) is at most 100 wt%.
53. The multilayer film according to claim 52, characterized in that, The core layer (CL) comprises, or is composed of, the following: (a) 18 to 22 wt% of metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the core layer (CL); and (b) 78 to 82 wt% of multimodal Ziegler-Natta catalyzed linear low-density polyethylene (ZNCP) based on the total weight of the core layer (CL); wherein The sum of the amounts of components (a) and (b) is at most 100 wt%.
54. The multilayer film according to claim 1, characterized in that, The multilayer membrane consists of a surface layer (SKL), a core layer (CL), and a sealing layer (SL); and / or The surface layer (SKL) contains Metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on the total weight of the surface layer (SKL). and Based on the total weight of the surface layer (SKL), there are 5 to 20 wt% LDPE, said LDPE having a content of 920 to 940 kg / m³. 3 The density is measured according to ASTM D792 within the range of 0.5 to 4.0 g / 10 min, and the MFR2 is measured at 190°C under a load of 2.16 kg according to ISO 1133.
55. The multilayer film according to claim 54, characterized in that, The surface layer (SKL) contains Metallocene-catalyzed multimodal polyethylene copolymers (MMCPs) comprising 82 to 93 wt% of the total weight of the surface layer (SKL); and LDPE of 7 to 18 wt% based on the total weight of the surface layer (SKL).
56. The multilayer film according to claim 54, characterized in that, The surface layer (SKL) contains Metallocene-catalyzed multimodal polyethylene copolymers (MMCPs) comprising 88 to 92 wt% of the total weight of the surface layer (SKL); and LDPE of 8 to 12 wt% based on the total weight of the surface layer (SKL).
57. The multilayer film according to claim 54, characterized in that, The LDPE has a strength of 930 to 936 kg / m³. 3 Density within the range measured according to ASTM D792.
58. The multilayer film according to claim 54, characterized in that, The LDPE has an MFR2 measured at 190°C under a load of 2.16 kg, in the range of 0.1 to 1.0 g / 10 min, according to the method of ISO 1133.
59. The multilayer film according to claim 1, characterized in that, The multilayer membrane consists of a surface layer (SKL), a core layer (CL), and a sealing layer (SL); and / or The sealing layer (SL) includes Based on 90 to 100 wt% of the total weight of the sealing layer (SL), a metallocene-catalyzed multimodal polyethylene copolymer (MMCP), or 50 to 70 wt% of the plastic body based on the total weight of the sealing layer (SL); and 30 to 50 wt% of multimodal metallocene-catalyzed linear low-density polyethylene based on the total weight of the sealing layer (SL).
60. The multilayer film according to claim 59, characterized in that, The sealing layer (SL) includes Metallocene-catalyzed multimodal polyethylene copolymer (MMCP) based on 95 to 100 wt% of the total weight of the sealing layer (SL).
61. The multilayer film according to claim 59, characterized in that, The sealing layer (SL) is composed of MMCP.
62. The multilayer film according to claim 59, characterized in that, The sealing layer (SL) includes 55 to 65 wt% of the plastic body based on the total weight of the sealing layer (SL); and 35 to 45 wt% of multimodal metallocene-catalyzed linear low-density polyethylene based on the total weight of the sealing layer (SL).
63. The multilayer film according to claim 59, characterized in that, The plastic body is a copolymer of ethylene and 1-octene.
64. The multilayer film according to claim 59, characterized in that, The plastic body has a strength of 860 to 910 kg / m³. 3 The density is measured according to ASTM D792 within the range of 0.5 to 10.0 g / 10 min, and the MFR2 is measured at 190°C under a load of 2.16 kg according to ISO 1133.
65. The multilayer film according to claim 64, characterized in that, The plastic body has a strength of 895 to 905 kg / m³. 3 Density within the range measured according to ASTM D792.
66. The multilayer film according to claim 64, characterized in that, The plastic body has an MFR2 measured at 190°C under a load of 2.16 kg, in the range of 1.0 to 1.5 g / 10 min, according to the method of ISO 1133.
67. The multilayer film according to claim 59, characterized in that, The multimodal metallocene-catalyzed linear low-density polyethylene is a bimodal ethylene / 1-butene / 1-hexene terpolymer.
68. The multilayer film according to claim 59, characterized in that, The multi-peaked metallocene-catalyzed linear low-density polyethylene has a strength of 910 to 930 kg / m³. 3 Density within the range measured according to ASTM D792; and MFR2 within the range of 0.5 to 2.0 g / 10 min measured at 190°C under a load of 2.16 kg according to ISO 1133.
69. The multilayer film according to claim 68, characterized in that, The multi-peaked metallocene-catalyzed linear low-density polyethylene has a strength of 916 to 925 kg / m³. 3 Density within the range measured according to ASTM D792.
70. The multilayer film according to claim 1, characterized in that, The thickness of the surface layer (SKL) of the multilayer film is in the range of 1 to 100 μm; and / or The core layer (CL) of the multilayer film has a thickness in the range of 10 to 200 μm; and / or The thickness of the sealing layer (SL) of the multilayer film is in the range of 1 to 50 μm; and / or The thickness of the multilayer film is in the range of 12 to 350 μm.
71. The multilayer film according to claim 70, characterized in that, The thickness of the surface layer (SKL) of the multilayer film is in the range of 5 to 80 μm.
72. The multilayer film according to claim 70, characterized in that, The thickness of the surface layer (SKL) of the multilayer film is in the range of 10 to 15 μm.
73. The multilayer film according to claim 70, characterized in that, The thickness of the core layer (CL) of the multilayer film is in the range of 20 to 80 μm.
74. The multilayer film according to claim 70, characterized in that, The thickness of the core layer (CL) of the multilayer film is in the range of 30 to 45 μm.
75. The multilayer film according to claim 70, characterized in that, The thickness of the sealing layer (SL) of the multilayer membrane is in the range of 5 to 25 μm.
76. The multilayer film according to claim 70, characterized in that, The thickness of the sealing layer (SL) of the multilayer film is in the range of 10 to 15 μm.
77. The multilayer film according to claim 70, characterized in that, The thickness of the multilayer film is in the range of 40 to 150 μm.
78. The multilayer film according to claim 70, characterized in that, The thickness of the multilayer film is in the range of 50 to 70 μm.
79. The multilayer film according to claim 1, characterized in that, The multilayer film has Longitudinal tensile modulus measured according to ISO 527-3 in the range of 200 to 500 MPa; and / or Transverse tensile modulus measured according to ISO 527-3 in the range of 250 to 600 MPa; and / or Dart strength measured according to ISO 7765-1 in the range of 500 to 1000 g.
80. The multilayer film according to claim 79, characterized in that, The multilayer film has a longitudinal tensile modulus measured according to ISO 527-3 in the range of 280 to 400 MPa.
81. The multilayer film according to claim 79, characterized in that, The multilayer film has a transverse tensile modulus measured according to ISO 527-3 in the range of 340 to 500 MPa.
82. The multilayer film according to claim 79, characterized in that, The multilayer film has a dart strength measured according to ISO 7765-1 in the range of 800 to 950 g.
83. The multilayer film according to claim 1, characterized in that, The multilayer film has a sealing initiation temperature in the range of 60 to 85°C.
84. The multilayer film according to claim 83, characterized in that, The multilayer film has a sealing initiation temperature in the range of 63 to 68°C.
85. The multilayer film according to claim 1, characterized in that, The multilayer film is composed of a polyethylene-based polymer.
86. Use of the multilayer film according to any one of the preceding claims as a packaging material.
87. The use according to claim 86, wherein the packaging material is used for food and / or medical products.
Citation Information
Patent Citations
Heat sealable blend of very low density polyethylene or plastomer with polypropylene based polymers and heat sealable film and articles made thereof
EP0575465A1
Procatalyst for ethylene polymer production, method for its preparation and use
EP0688794A1
A process for the production of a linear low-density polyethylene composition
EP1378528A1
Process for preparing polyethylene
WO1996018662A1
Polyolefin composition with molecular weight maximum occuring in that part of the composition that has the highest comonomer content
WO1997044371A1